Nanotechnological Advances for Cutaneous Release of Tretinoin: An Approach to Minimize Side Effects and Improve Therapeutic Efficacy - Raminelli, Ana C. P.; Romero, Valeria; Semreen, Mohammad H.; Leonardi, Gislaine R. (Current Medicinal Chemistry, 2018)
Background: The clinical efficacy of the topical tretinoin is widely studied and has been well established for many therapeutic interventions, among some, photoaging, acne, and melasma. However, the side effects, mainly cutaneous irritation, erythema, xerosis and peeling, remain major obstacle to the patient compliance. Besides, the insight regarding the drug delivery profile is essential to understand the therapeutic action of the drug. Methods: Through bibliographic research in databases we highlight further advances and an update on tretinoin delivery systems such as liposomes, niosomes, solid lipid nanoparticles, nanostructured lipid carriers, cyclodextrins, nanostructured polymers and other technological systems that reduce its side effects and improve the permeation profile to potentiate efficacy and drug safety on the skin. Results: Pharmaceutical preparations were developed and evaluated for permeability in in vitro models using pig ear, snake, mouse and human skin, and potential for irritation was also verified using release systems for tretinoin and compared to available commercial formulations. Overall results indicated the composition, charge and size of the system influences the tretinoin delivery, modulating the type of release and its retention. Small unilamellar vesicles promoted greater cutaneous delivery of tretinoin. Negative charge, for both liposomes and niosomes, can improve pig skin hydration as well as the tretinoin retention. The quantity of solid lipids and the type of oil used in the composition of solid lipid nanoparticles and nanostructured lipid carriers affected percutaneous drug delivery. Conclusion: As evident from the literature, the tretinoin technological delivery systems consist an innovative and potential management for increasing the patient compliance presenting safety and efficacy.
Keywords: nanotechnology